A communicative community of agents - Lipowska, Dorota (Lingua Posnaniensis, 2012)
Computer modelling is becoming an increasingly important tool for researching the problem of origin and evolution of language. Afundamental technique is that of multi-agent modelling, which simulates a system of dynamically interacting individuals called agents, equipped with strictly defined properties and rules governing their behaviour or evolution. In such a population (a communicative community), as a result only of local interactions between agents, a process of self-organization occurs and some kind of global property emerges, such as linguistic coherence. Presented here are two models of the naming game type, in which agents exchange names of objects, gradually establishing a common vocabulary. In the evolutionary version there was observed a very strong link between biological and linguistic processes, being a clear manifestation of Baldwin’s effect - genetic assimilation of the ability to learn (a language, for example). In the multi-object version the development of homonymy and synonymy was studied, as well as the effect of noise on a developing language.